2022
DOI: 10.22271/phyto.2022.v11.i5a.14501
|View full text |Cite
|
Sign up to set email alerts
|

The species of genus fagonia in Libya: (A comprehensive review)

Abstract: The Plants of the genus Fagonia have been broadly utilized as adjunctive therapy, to treat several conditions involving high fever, diabetes, asthma, stoma chache, dental pain, and renal problems using their aqueous extracts as medicines. This genus is a valuable source that comprises a variety of Triterpenes, flavonoids, and Saponins. The herbal chemistry as well as the biological action of Fagonia species have been a candidate for many researchers. The in vivo pharmacological screening of their extracts has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…This suggests that FASEE has a potent cytotoxic effect against Ehrlich carcinoma (11). In contrast to the results of the current study, Alamami et al reported that an alcoholic and aqueous extracts of Fagonia taeckholmiana revealed no significant anti-carcinogenic effect on neither human liver carcinoma cells (HEPG2) nor human glioblastoma cells (U-251) (26). In addition, Albalawi et al concluded that an extract of Fagonia tenuifolia had little anti-cancer effect on non-small cell lung cancer cells (NCI-H460) (27).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This suggests that FASEE has a potent cytotoxic effect against Ehrlich carcinoma (11). In contrast to the results of the current study, Alamami et al reported that an alcoholic and aqueous extracts of Fagonia taeckholmiana revealed no significant anti-carcinogenic effect on neither human liver carcinoma cells (HEPG2) nor human glioblastoma cells (U-251) (26). In addition, Albalawi et al concluded that an extract of Fagonia tenuifolia had little anti-cancer effect on non-small cell lung cancer cells (NCI-H460) (27).…”
Section: Discussioncontrasting
confidence: 99%
“…Flavonoids have been found to possess anti-mutagenic and anti-malignant properties. Additionally, flavonoids contribute to cancer chemoprevention through their impacts on angiogenesis and signal transduction in cell growth (26). A number of trials were executed in order to detect the effective dose of Fagonia arabica.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation